Pengamatan Waktu Pelayanan Operator Pintu Tol dengan Uji Hipotesis Analysis of Variance (ANOVA) (Studi Kasus: Gerbang Tol Ancol Timur, Jakarta Utara - Hendy Tannady; Wahyu Eka Munardi (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Highway facilities are the most used facilities people in Jakarta city to avoid the traffic jam. this paper will present time service of the operator for each highway gate at Gerbang Tol Ancol Timur, North Jakarta. This research conducted to determine whether there is a significant difference in time service for each highway gate with ANOVA hypothesis analysis. The researcher also uses software to do some calculate in ANOVA hypothesis analysis. The result from observation processed using the software and formula, the value of P is 0,097 with software calculation and the value of F-arithmetic is 2,4487 with formula calculation. from that data, it can be concluded that there are no significant differences in time service for each highway gate, because P > α (0,05) and F-table (3.19506) > F-arithmetic.Keywords: ANOVA, Minitab, Gerbang Ancol Timur.